Konsep Pemikiran Pendidikan Toleransi Fethullah Gulen - Muhammad Anas Ma'arif (Tribakti: Jurnal Pemikiran Keislaman, 2019)
The purpose of writing this article is to explain the concepts, thoughts and application of education according to Gulen. Such as the integration of Islam and science, the internalization of love and tolerance, modern tasawuf, the golden generation, Islam rahmatan lil alamin and human services with hizmet. This paper uses the library research method by collecting books, journal articles, original web and writings that are relevant to the themes discussed. Finding: Fethullah Gulen is an influential figure in the world of education as evidenced by schools managed by Gulen Movement established in 130 countries. Gulen applies hizmet as a missionary service to serve people who are engaged in the world of education. Modern sufist education models that integrate esoteric aspects and exoteric aspects. Teaches love in education, tolerance by dialogue and integrating Islam and science as a whole. All of them are to form a golden generation that is able to answer the changing times and become a man of love and a harmonious life.